A bibliometric analysis of scientific production in lean supply. Issue 1 (2018) - Endler, Kellen Dayelle; Scarpin, Cassius Tadeu; Steiner, Maria Teresinha Arns
A lean supply chain arrangement should provide flow of goods, services and technology from the supplier of raw materials to the customer without waste. Lean supply is an increasingly visible area not only at the theoretical level, but also in terms of practical application in companies offering products or services. Thus, scientific progress in this field of study is fundamentally derived from the knowledge available about it, which is the result of investigations and interactions by researchers over time. The main objective of this study, therefore, is to conduct a quantitative analysis of scientific production on lean supply between 1992 and 2016. The work was carried out with a methodical review of the literature, relying on bibliometric techniques, by consulting the databases ISI Web of Knowledge and Scopus, and their treatment by Bibexcel and Pajek softwares. For the research, the term 'lean supply' was used as a key expression, generating a sample of 211 published articles. Descriptive statistical results were presented, identifying the authors, articles and journals most frequently referenced by scholars worldwide. At the end of the study, recent papers of the sample were classified and analysed based on research methods and industry sectors.